Training martian seismologists for InSight. Issue 5 (1st October 2018) - Fernando, Benjamin; Tsekhmistrenko, Maria; Hosseini, Kasra
Abstract : Benjamin Fernando, Kasra Hosseini and Maria Tsekhmistrenko describe how blind testing is helping to train martian seismologists. Abstract : Benjamin Fernando, Kasra Hosseini and Maria Tsekhmistrenko describe how blind testing is helping to train martian seismologists.